Social capital in the development of innovation: The Costa Rican agri-food industry case - Soto Kiewit, Luis Diego; Segura Jiménez, Alexis; Aguilar Mata, Guillermo; Medina Díaz, Rebeca; Díaz Fallas, Noely; Arias Alfaro, Karen (Cooperativismo & Desarrollo, 2017)
Introduction: In the global context, innovation has acquired great importance and stimulates the interest of several areas of scientific knowledge. As is the case with Sociology, which is paying special attention to the social dimensions that make up innovative processes. Methodology: Applying a qualitative approach and the life stories technique, the processes and experiences, that is, the life trajectories of the innovative people of the Costa Rican agri-food industry are recorded, constructed, reviewed and analyzed. Results: In the processes of recording, revision and interpretation of life stories it is possible to detect the construction and adoption of resources shaped by the interaction with different agents, as well as the way in which they contributed to the development of innovations. Conclusions: In the cases investigated, innovation isn’t a product of an individual process made by isolated, asocial or gifted individuals, but of social persons. Around these individuals, one may find a series of contributions, in the form of social capital, obtained from the bonds and relationships carried out with other people, either with their reference groups, mentors or peer groups.